Correction: Yamarthi et al. Sepia pharaonis Ink Mitigates Dehydroepiandrosterone-Induced Insulin Resistance in Mouse Model of Polycystic Ovarian Syndrome. Pathophysiology 2024, 31, 408–419 - Prathyusha Yamarthi; Rama Satyasri Kotipalli; Samatasai Patnaik; Kv Veena; Muralidharan Kathirvel; Rajkumar Vutukuri; Manjula Bhanoori (Pathophysiology)
Error in Figure [...]